PENGELOLAAN BIG DATA: INOVASI SOLUSI DAN TANTANGAN DALAM ERA INFORMASI MODERN - Dela Arum Lestari; Muhammad Irwan Padli Nasution (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The rapid development of information technology has led to the birth of the Big Data era, a condition in which data is available in large quantities, diverse, and moving quickly. Big Data is an important resource that can be utilized to improve operational efficiency, strengthen decision-making, and drive innovation, both in the business and government sectors. This study uses a literature study method by analyzing various relevant scientific references to identify the use, challenges, and solutions in managing Big Data in the modern information era. The results of the study show that the main challenges in implementing Big Data include limited infrastructure, human resource competency, data security, and suboptimal integration and standardization between agencies. Therefore, a collaborative strategy is needed between the government, private sector, and educational institutions to build an inclusive, safe, and sustainable data ecosystem. With proper management, Big Data has great potential as a major driver of national digital transformation.